2020
DOI: 10.1186/s12876-020-01291-2
|View full text |Cite
|
Sign up to set email alerts
|

A cross-sectional study of nausea in functional abdominal pain: relation to mucosal mast cells and psychological functioning

Abstract: Background Nausea is a common symptom in youth with chronic abdominal pain. The aims of the current study were to assess: 1) the frequency of nausea in patients with functional dyspepsia (FD) and irritable bowel syndrome (IBS), respectively, as defined by Rome IV criteria; and, 2) relationships between nausea and mucosal inflammation as defined by antral and duodenal eosinophil and mast cell densities. A secondary aim was to assess relationships between nausea and other gastrointestinal symptoms, non-gastroint… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 26 publications
0
9
0
Order By: Relevance
“…We therefore hypothesized that increased gastric vagal activity may contribute to the changes in affective behavior and nociception associated with FD, and that gastric mast cells may have a mechanistic role, given their well-established functional relationship with neurons (14). Several studies have reported an increase in mucosal mast cells in the upper gastrointestinal tract in both children and adults with FD, similar to what has been described in patients with IBS (15)(16)(17). In the current study, we tested these hypotheses using a previously validated rat model of FD in which mild gastric irritation in neonatal rats induces a state of persistent gastric hyperalgesia, impaired gastric motility, and anxiety-like and depression-like behavior in adulthood, which was associated with brain alterations (7,18).…”
Section: Introductionmentioning
confidence: 80%
“…We therefore hypothesized that increased gastric vagal activity may contribute to the changes in affective behavior and nociception associated with FD, and that gastric mast cells may have a mechanistic role, given their well-established functional relationship with neurons (14). Several studies have reported an increase in mucosal mast cells in the upper gastrointestinal tract in both children and adults with FD, similar to what has been described in patients with IBS (15)(16)(17). In the current study, we tested these hypotheses using a previously validated rat model of FD in which mild gastric irritation in neonatal rats induces a state of persistent gastric hyperalgesia, impaired gastric motility, and anxiety-like and depression-like behavior in adulthood, which was associated with brain alterations (7,18).…”
Section: Introductionmentioning
confidence: 80%
“…Nausea has been associated with worse abdominal pain and gastrointestinal symptoms, somatic symptoms, sleep disturbances, depression, anxiety, disability, poor school and social functioning, school absences, and poorer QOL. [14][15][16][17] Nausea also predicts a higher rate of persistence of gastrointestinal and somatic symptoms, anxiety, and depression into adulthood. 14 As such, nausea may be an important treatment target in FAPDs.…”
Section: Introductionmentioning
confidence: 99%
“…As the role of mast cells in the pathology of gastrointestinal disease is still evolving, there are currently no specific criteria for their number in the normal stomach (Doyle et al, 2014; Ramsay et al, 2010; Zanelli et al, 2021). Quantification of mast cells in the healthy gastric mucosa reveals a wide range from fewer than 15 to more than 50 per HPF (Friesen et al, 2020, 2021; Hahn & Hornick, 2007; Jakate et al, 2006; Siegert et al, 2004), which makes it difficult to specify a cut‐off value for differentiating normal from pathological mucosa. In systemic mastocytosis, mast cells are often found in confluent sheets and aggregates of over 100 cells per HPF (Ramsay et al, 2010).…”
Section: Resultsmentioning
confidence: 99%
“…Quantification of mast cells in the healthy gastric mucosa reveals a wide range from fewer than 15 to more than 50 per HPF (Friesen et al, 2020(Friesen et al, , 2021Hahn & Hornick, 2007;Jakate et al, 2006;Siegert et al, 2004), which makes it difficult to specify a cut-off value for differentiating normal from pathological mucosa. In systemic mastocytosis, mast cells are often found in confluent sheets and aggregates of over 100 cells per HPF (Ramsay et al, 2010).…”
Section: F I G U R E 2 Legend On Next Pagementioning
confidence: 99%